(untitled) (Perner’s Contacts, 2013)
The post deals with an issue of optimization of transport serviceability by public passenger transport. The first part is about position of public passenger transport in Slovakia. Another part of the post describes requirements for ensuring transport serviceability in regional public passenger transport.